2009
DOI: 10.1111/j.1754-9485.2009.02039.x
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience in 115 patients with the retrievable Cook Celect vena cava filter

Abstract: SummaryThe aim of this study was to evaluate our experience with the retrievable Cook Celect inferior vena cava (IVC) filter (William Cook, Europe) with regard to insertion, efficiency, ease of retrieval, and any associated complications. A retrospective review was performed of 115 patients (41 female, 74 male, mean age 47.97 years) who underwent Cook Celect IVC filter insertion between December 2005 and October 2007. Filter insertion was successful in all patients. Of the 115 filters inserted, 57 have been su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 18 publications
0
11
1
Order By: Relevance
“…In the previously quoted study, the Celect filter was found to have a mean dwell time of 114.9 days (range 14-267 days) in successfully retrieved filters. 20 In our case, the patient's filter had been in place for five months when he became symptomatic, and nine months at the time of surgery.…”
Section: Discussionmentioning
confidence: 93%
“…In the previously quoted study, the Celect filter was found to have a mean dwell time of 114.9 days (range 14-267 days) in successfully retrieved filters. 20 In our case, the patient's filter had been in place for five months when he became symptomatic, and nine months at the time of surgery.…”
Section: Discussionmentioning
confidence: 93%
“…A proportion of retrievable IVC filters cannot be removed by the conventional snare or cone recovery techniques. Two larger Australian studies have shown a filter retrieval success rate of 92–93% . The main factors associated with complicated or unsuccessful retrieval are tilting of the filter, embedding of the filter hook into the wall and prolonged dwell times …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Use of both filters is well described in the literature. [7][8][9][10] Initial studies have analyzed the retrievability of the modified filter and have demonstrated excellent results with reported retrieval rates Ͼ90%, which compares favorably with the older standard model. However, no study has directly compared the clinical performance of the modified vs standard filter.…”
mentioning
confidence: 97%